Natamycin content and quality evaluation of yoghurt from small- and large-scale brands in Turkey - Dervisoglu, Muhammet; Gul, Osman; Aydemir, Oguz; Yazici, Fehmi; Kahyaoglu, Talip (TAYLOR & FRANCIS LTD, 2014)
In this study, the presence of natamycin and quality parameters of yoghurt samples manufactured by small- and large-scale dairy firms in Turkey were investigated. Physicochemical and microbiological results revealed that, except Lactobacillus bulgaricus and Streptococcus thermophilus counts, the majority of the yoghurts manufactured by small-scale dairy firms were found to be out of the limits. Natamycin was detected in 31 and 2 yoghurt samples from small- and large-scale brands, respectively. The levels of natamycin in small-scale brand yoghurts were higher than those in large-scale brand yoghurts. Of the analysed samples, 42.3% did not comply with the Turkish Food Codex.
Keywords: natamycin; yoghurt; product quality; preservative; microbiology; MICROBIOLOGICAL QUALITY; BENZOIC-ACID; SORBIC ACID; CHEESE; Chemistry; Food Science & Technology; Toxicology